Rossiia Voskrese . Rossiia Voskrese . Russia Resurrected . Россия Воскресе - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. A documentary about the significance of culture in Russian society. (Part 2) Featured in the program: Voznesenskii, Andrei (Poet); Viktiuk, Roman (Director); Kedrov, Konstantin Aleksandrovich (Poet) Contributors: Misiavichus, Ionas (Director); Slabyn'ko, Oleg Aleksandrovich (Anchor) Документальный фильм о значении культуры для российского общества. (Часть 2). В программе участвуют: Вознесенский, Андрей (Поэт); Виктюк, Роман (Режиссер); Кедров, Константин Александрович (Поэт) Создатели: Мисявичус, Йонас (Режиссер); Слабынько, Олег Александрович (Ведущий/Ведущая)